Assessment of radiation hazards from natural radionuclide activity in quarry sites and surrounding soils in Osun State, Southwest Nigeria - Olubusayo F. Oladejo; Stephen F. Olukotun; Abdulfatai B. Rufai; Manny Mathuthu (Scientific Reports)
Abstract This study assessed the radioactivity levels of naturally occurring radioactive materials (NORMs), specifically 40K, 232Th, and 238U, in quarry products and surrounding soils from four major commercial quarry sites in Osun State, Nigeria, using gamma spectroscopic technique. The average activity con40centrations of K, 232Th, and 238U in the quarry products are 332.55 ± 28.8, 9.72 ± 1.0, and 11.35 ± 1.0 Bq/kg, respectively, all below global averages. Radiation risk indices, including radium equivalent levels, effective dose rates, absorbed dose rates, gamma radioactivity level index, internal and external hazard indices, and gonadal dose equivalent, were evaluated. The radium equivalent levels ranged from 48.77 to 53.25 Bq/kg, well below the global limit of 370 Bq/kg, while the absorbed dose rates were 40% lower than the global average. Total effective dose rates and hazard indices were also significantly below safety thresholds, indicating negligible radiation threats. Statistical analysis revealed strong correlations between 40K and radiological indices, showing its dominant influence on overall radiation risk. Correlation and hierarchical cluster analysis further affirmed that the evaluated radiological risks were dependent on the radionuclides measured concentrations. The results conclude that both the quarry products and surrounding soils pose no significant radiation hazards, rendering them safe for construction and human activities.